An Ir-doped TiO2-SrTiO3 heterostructure catalyst, its preparation method and application

CN122879752APending Publication Date: 2026-10-09NORTHEAST NORMAL UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611298365.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

但该类方案仅为表面异质结结构,Ir以纳米颗粒或薄膜形式负载于载体表面,未实现体相晶格原位掺杂与原子级键合,无法形成稳定的共格/半共格界面

Benefits of technology

采用本申请制备方法制备的Ir掺杂TiO2-SrTiO3异质结构催化剂,Ir掺杂量为1–3mmol时,材料形成SrTiO3-TiO2异质结构;Ir掺杂量为4 mmol时,材料以TiO2为主相。并且随Ir掺杂量提升,Sr元素分布降低,Ti元素分布增加。本申请催化剂材料为纳米多孔结构,颗粒分布均匀,有利于电化学反应传质、电荷转移与气体释放。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879752A_ABST
    Figure CN122879752A_ABST
Patent Text Reader

Abstract

The application discloses an Ir-doped TiO2-SrTiO3 heterostructure catalyst and a preparation method and application thereof, and belongs to the technical field of water electrolysis hydrogen production electrocatalytic materials, and comprises the following steps: dissolving a titanium source, a strontium source and an iridium source in an alkali solution, stirring and reacting to obtain a first perovskite precursor; performing high-temperature hydrothermal reaction on the first precursor to obtain a second composite precursor; placing the second composite precursor in a nitric acid solution for ultrasonic etching, washing with deionized water and ethanol after reaction, and drying to obtain an Ir-doped SrTiO3-TiO2 heterostructure catalyst. The iridium-based heterostructure catalyst prepared by the method has excellent electrocatalytic activity and long-term structural stability for water electrolysis oxygen evolution reaction (OER) under acidic conditions, and can effectively replace traditional high-load iridium-based catalysts. The preparation process is simple, the parameters are controllable, the cycle is short, and the method is suitable for industrial large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrocatalytic materials technology for hydrogen production by water electrolysis, specifically relating to an Ir-doped TiO2-SrTiO3 heterostructure catalyst for acidic OER, its preparation method, and its application. Background Technology

[0002] Proton exchange membrane electrolysis (PEMWE) is a core technology for producing high-purity hydrogen, and the anodic oxygen evolution reaction (OER) is a key step limiting electrolysis efficiency. OER reactions under acidic conditions require highly efficient catalysts to reduce overpotential and increase current density. Ir-based catalysts are currently the most widely used catalytic materials in the field of acidic OER, possessing high conductivity, a suitable d-electron structure, and good chemical stability, enabling OER catalysis with low overpotential and high current density.

[0003] Existing Ir-based catalysts suffer from insufficient long-term stability, with the following key limiting factors: First, the involvement of lattice oxygen leads to structural collapse. At high potentials, the participation of Ir lattice oxygen in the OER reaction causes lattice structure destruction and loss of active sites. Second, surface Ir atoms dissolve or migrate. In acidic electrolytes, surface Ir atoms are easily dissolved or migrated, resulting in a reduction in active sites and decreased crystal structure stability. Therefore, simultaneously improving the activity and structural stability of acidic OER catalysts is a pressing technical challenge that needs to be addressed in this field.

[0004] To address the aforementioned issues, existing technologies optimize the performance of Ir-based catalysts through morphology control, atomic doping, support modification, and heterostructure construction. Among these, catalyst modification based on the interfacial electronic interactions between titanium-based oxides and Ir is a key research direction in the industry.

[0005] For example, in a single TiO2-supported Ir system, the acidic stability of TiO2 helps mitigate Ir corrosion and dissolution. However, conventional impregnation, precipitation, and deposition processes only cause Ir particles to adhere to the support surface, without atomic-level lattice anchoring. The interfacial interaction between Ir and TiO2 is weak, and Ir easily dissolves, migrates, and aggregates at high potentials. The single TiO2 lattice lacks sufficient ability to regulate the electronic structure of Ir and cannot effectively suppress the degradation reaction involving lattice oxygen (LOM pathway), resulting in significant catalyst degradation issues during long-term operation.

[0006] There are also single-SrTiO3 perovskite lattice-doped Ir systems, such as CN201811193533.0, which discloses a single-phase SrTi(Ir)O3 perovskite solid solution catalyst. This catalyst utilizes the confinement effect of the rigid three-dimensional SrTiO3 lattice to dope Ir atoms at the B sites of the perovskite, mitigating Ir atom migration and aggregation to some extent, thus improving catalytic activity and basic stability. However, this type of single-phase perovskite system has inherent technical limitations: the single-phase solid solution has limited electronic control freedom, making it difficult to further optimize the OER energy barrier; SrTiO3 has poor intrinsic conductivity, making it unsuitable for high current density PEMWE conditions; and the single-phase structure lacks heterogeneous interface synergy, failing to fundamentally suppress the LOM pathway, thus the simultaneous breakthrough of activity and stability is fundamentally constrained at the structural level.

[0007] Existing research further attempts to construct IrO x / TiO x Heterojunctions utilize built-in electric fields to control the electronic structure. However, these schemes are merely surface heterojunctions, with Ir loaded onto the support surface in the form of nanoparticles or thin films. They fail to achieve in-situ bulk lattice doping and atomic-level bonding, thus preventing the formation of stable coherent / semi-coherent interfaces. Their interface electronic control depth is limited, and their structural stability is poor. Long-term high-potential operation easily leads to interface delamination and structural reconstruction, making long-term stable catalysis impossible.

[0008] In summary, existing technologies can only achieve single-support loading, single-lattice doping, surface heterojunctions, or physical composite modification. No technical solution has yet been developed that can achieve simultaneous and precise doping of Ir atoms in a dual-lattice structure of TiO2 and SrTiO3, construct atomically bonded heterojunction interfaces, and simultaneously enhance OER catalytic activity and structural stability through two-phase electronic synergistic regulation. To address this technological gap, this invention proposes a corresponding catalyst modification scheme. Summary of the Invention

[0009] To address the shortcomings of existing technologies, this invention provides an Ir-doped SrTiO3-TiO2 heterostructure catalyst and its preparation method. By constructing a SrTiO3-TiO2 heterostructure through Ir doping, the catalytic activity and stability of acidic OER are simultaneously optimized. The catalytic system is compatible with both adsorbent evolution mechanism (AEM) and lattice oxygen participation mechanism (LOM), achieving low overpotential, high current density, and long-term stable operation, providing a new pathway for the design of novel acidic OER catalysts. This method is simple to operate, with controllable parameters, suitable for large-scale preparation. The prepared catalyst exhibits high activity, high stability, low iridium loading, and high-quality activity, and can be directly used as an anode in proton exchange membrane water electrolysis (PEMWE).

[0010] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing an Ir-doped TiO2-SrTiO3 heterostructure catalyst includes the following steps: S1. Weigh out titanium source, strontium source and iridium source, add them to dilute alkaline solution, stir and react at room temperature to obtain the first perovskite precursor; S2. Heat the first perovskite precursor until the solution turns blue to activate the precursor. S3. The activated precursor is subjected to a high-temperature hydrothermal reaction to obtain the second composite precursor. S4. Add HNO3 solution to the second composite precursor, sonicate the reaction, and wash and dry after the reaction to obtain Ir-doped SrTiO3-TiO2 heterostructure catalyst.

[0011] In the preparation method described above, in step S1, the titanium source is TiO2, the strontium source is one of Sr(NO3)2 and Sr(OH)2, and the iridium source is H2IrCl6; the molar ratio of titanium source, strontium source and iridium source is 3~1:5:1~3.

[0012] Preferably, the molar ratio of titanium source, strontium source, and iridium source is 3:5:2.

[0013] In the preparation method described above, the dilute alkaline solution in S1 is a 1M KOH solution, the reaction is carried out at room temperature, and the reaction time is 10–24 hours.

[0014] In the preparation method described above, the endpoint of the reaction in S2 is determined by the change of the solution from light blue to dark blue.

[0015] In the preparation method described above, the hydrothermal reaction temperature in S3 is 100–400℃, and the temperature is maintained for 12–76 hours.

[0016] Preferably, the reaction temperature is 300℃ and the reaction time is 36 hours.

[0017] In the preparation method described above, the HNO3 solution in S4 is a nitric acid aqueous solution with a mass fraction of 25-35%, and the ratio of the total amount of titanium source, strontium source and iridium source to HNO3 solution is 1:1 to 1:5 mmol / mL. The reaction is carried out by sonication for 10-60 minutes, and the solution is washed with deionized water and ethanol after the reaction is completed.

[0018] Preferably, the ratio of the total amount of titanium source, strontium source and iridium source to HNO3 solution is 1:5, and the ultrasonic time is 60 minutes.

[0019] This invention provides an Ir-doped TiO2-SrTiO3 heterostructure catalyst, which is prepared by the method described above and has a nanoporous structure with uniform particle distribution.

[0020] This invention also provides the application of the Ir-doped TiO2-SrTiO3 heterostructure catalyst in electrocatalytic water splitting for oxygen production. The catalyst is used as the anodic oxygen evolution catalyst in a proton exchange membrane water electrolysis system for electrocatalytic water oxidation under acidic conditions. Under low iridium loading conditions, it can effectively reduce the oxygen evolution overpotential and improve the electrocatalytic reaction kinetics. At the same time, it has excellent long-term service stability and can achieve efficient and durable electrocatalytic water splitting for oxygen production.

[0021] Due to the adoption of the above technical solution, the technical effects achieved by the present invention are as follows: The Ir-doped TiO2-SrTiO3 heterostructure catalyst prepared by the method described in this application forms an SrTiO3-TiO2 heterostructure when the Ir doping amount is 1–3 mmol; when the Ir doping amount is 4 mmol, the material is dominated by TiO2. Furthermore, with increasing Ir doping amount, the Sr element distribution decreases while the Ti element distribution increases. The catalyst material of this application has a nanoporous structure with uniform particle distribution, which is beneficial for mass transfer, charge transfer, and gas release in electrochemical reactions.

[0022] In the electrochemical testing of the catalyst in this application, at 0.5 mol L... -1 The catalyst prepared in sulfuric acid electrolyte with a Ti source to Ir source molar ratio of 3:2 achieved a current density of 10 mA cm⁻¹. -2 With an overpotential of only 260 mV, it exhibits optimal catalytic activity; the Ir loading is as low as ~0.122 mg cm⁻¹. -2 , in 1 A cm -2 After 1300 hours of continuous operation at the current density, the degradation rate was only 0.0296 mVh. -1 Its stability is far superior to that of commercial IrO2.

[0023] The iridium-based heterostructure catalyst prepared by this method exhibits excellent electrocatalytic activity and long-term structural stability in the oxygen evolution reaction (OER) of water under acidic conditions, and can effectively replace traditional highly supported iridium-based catalysts. The preparation process of this invention is simple, with controllable parameters and a short cycle time, making it suitable for large-scale industrial production. Attached Figure Description

[0024] Figure 1 XRD comparison images of SrTiO3-TiO2 heterostructures with different Ir contents; Figure 2 XPS schematic diagram of a physically mixed SrTiO3-TiO2 heterostructure; Figure 3 STEM and EDS schematic diagrams of SrTiO3-TiO2 heterostructures with different Ir contents; Figure 4The electrochemical performance of SrTiO3-TiO2 heterostructures under different Ir contents was tested using a three-electrode method. Figure 5 The three-electrode electrochemical performance of SrTiO3-TiO2 heterostructure at different calcination temperatures was tested. Figure 6 For STO-2 and commercial IrO2 in 1A cm -2 PEMWE activity test results; Figure 7 For STO-2 and commercial IrO2 in 1A cm -2 The results of the PEMWE stability test. Detailed Implementation

[0025] To enable those skilled in the art to better understand the present invention, the present invention will be further described in detail below. The specific embodiments listed below are merely descriptions of the principles and features of the present invention, and the examples are only for explaining the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0026] The method for preparing Ir-doped SrTiO3-TiO2 heterostructure catalyst provided by this invention includes the following steps: S1. Precursor mixing and activation Weigh out titanium source, strontium source, and iridium source, add 100 mL of 1 M KOH solution, and stir magnetically at room temperature for 10–24 hours to obtain the first perovskite precursor; S2. Heat the first perovskite precursor in an oil bath at 100–130°C until the solution turns blue, thus completing the precursor activation.

[0027] In a preferred embodiment, the titanium source is TiO2, the strontium source is Sr(NO3)2, and the iridium source is H2IrCl6; the amounts of titanium source, strontium source, and iridium source added are 3 mmol, 5 mmol, and 2 mmol, respectively; the oil bath time is about 60 min, and the reaction endpoint is when the solution changes from light blue to dark blue.

[0028] S3. High-temperature hydrothermal reaction The activated precursor was transferred into a polytetrafluoroethylene high-pressure reactor, heated to 100–400°C, held at that temperature for 12–76 hours, and then dried after natural cooling to room temperature to obtain the second composite precursor.

[0029] In a preferred embodiment, the reaction temperature is 300°C and the reaction time is 36 hours.

[0030] S4. Acid etching and purification Add 10–50 mL of 30% HNO3 to the second composite precursor and sonicate for 10–60 minutes. After the reaction is complete, wash three times each with deionized water and ethanol, and dry to obtain the Ir-doped SrTiO3-TiO2 heterostructure catalyst.

[0031] In a preferred embodiment, 30% HNO3 is added in a volume of 50 mL, and the sonication time is 60 minutes.

[0032] All raw materials used in the examples were commercially available conventional chemicals. The effect of Ir molar ratio of 0-5 mmol on catalyst performance was investigated.

[0033] Example 1 (STO-0, no Ir doping) Weigh 5 mmol TiO2 and 5 mmol Sr(NO3)2 and dissolve them in 100 mL 1M KOH solution. Stir magnetically at room temperature for 24 hours to obtain the first perovskite precursor. Heat the first precursor in an oil bath at 100℃ until the solution turns blue. Transfer it to a high-pressure reactor and keep it at 300℃ for 12 hours. After natural cooling, filter and dry to obtain the second composite precursor. Add 50 mL 30% HNO3 to the second composite precursor, sonicate for 60 minutes, wash three times each with deionized water and ethanol, and dry to obtain the STO-0 catalyst.

[0034] Example 2 (STO-1, Ir doping 1 mmol) Weigh 4 mmol TiO2, 5 mmol Sr(NO3)2, and 1 mmol H2IrCl6 and dissolve them in 100 mL of 1 M KOH solution. Stir magnetically at room temperature for 24 hours to obtain the first perovskite precursor. Heat the first precursor in an oil bath at 100 °C until the solution turns blue. Transfer it to a high-pressure reactor and keep it at 300 °C for 12 hours. After natural cooling, filter and dry to obtain the second composite precursor. Add 50 mL of 30% HNO3 to the second precursor, sonicate for 60 minutes, wash three times each with deionized water and ethanol, and dry to obtain the STO-1 catalyst.

[0035] Example 3 (STO-2, Ir doped 2 mmol) Weigh 3 mmol TiO2, 5 mmol Sr(NO3)2, and 2 mmol H2IrCl6 and dissolve them in 100 mL of 1 M KOH solution. Stir magnetically at room temperature for 24 hours to obtain the first perovskite precursor. Heat the first precursor in an oil bath at 100 °C until the solution turns blue. Transfer it to a high-pressure reactor and keep it at 300 °C for 12 hours. After natural cooling, filter and dry to obtain the second composite precursor. Add 50 mL of 30% HNO3 to the second precursor, sonicate for 60 minutes, wash three times each with deionized water and ethanol, and dry to obtain the STO-2 catalyst.

[0036] Example 4 (STO-3, Ir doped 3 mmol) Weigh 2 mmol TiO2, 5 mmol Sr(NO3)2, and 3 mmol H2IrCl6 and dissolve them in 100 mL of 1 M KOH solution. Stir magnetically at room temperature for 24 hours to obtain the first perovskite precursor. Heat the first precursor in an oil bath at 100 °C until the solution turns blue. Transfer it to a high-pressure reactor and keep it at 300 °C for 12 hours. After natural cooling, filter and dry to obtain the second composite precursor. Add 50 mL of 30% HNO3 to the second composite precursor, sonicate for 60 minutes, wash three times each with deionized water and ethanol, and dry to obtain the STO-3 catalyst.

[0037] Example 5 (STO-4, Ir doped 4 mmol) Weigh 1 mmol TiO2, 5 mmol Sr(NO3)2, and 4 mmol H2IrCl6 and dissolve them in 100 mL of 1 M KOH solution. Stir magnetically at room temperature for 24 hours to obtain the first perovskite precursor. Heat the first precursor in an oil bath at 100 °C until the solution turns blue. Transfer it to a high-pressure reactor and keep it at 300 °C for 12 hours. After natural cooling, filter and dry to obtain the second composite precursor. Add 50 mL of 30% HNO3 to the second composite precursor, sonicate for 60 minutes, wash three times each with deionized water and ethanol, and dry to obtain the STO-4 catalyst.

[0038] Example 6 (M-STO, physically mixed sample) Weigh out 5 mmol TiO2 and 5 mmol SrTiO3, mix them thoroughly and grind them to obtain the product (M-STO).

[0039] Comparative Example Comparative Example 1 (STO-2-300, Ir doped 2 mmol) The STO-2 catalyst was obtained by drying in Example 3 and then calcined in air at 300°C for 3 h in a tube furnace.

[0040] Comparative Example 2 (STO-2-400, Ir doped 2 mmol) The STO-2 catalyst was obtained by drying in Example 3 and then calcined in air at 400°C for 3 h in a tube furnace.

[0041] Experimental Example 1 A certain amount of the catalysts prepared in Examples 1-6 were weighed and XRD was detected. The results are as follows: Figure 1As shown, it can be observed that the prepared samples exhibit a certain relationship with the amount of Ir doping. Without Ir doping, the material is a single-phase SrTiO3; with 1–3 mmol of Ir doping, it is a SrTiO3-TiO2 heterostructure; and with 4 mmol of Ir doping, it is a single-phase TiO2. Excessive Ir disrupts the perovskite structure. Meanwhile, as... Figure 2 The XPS test results show that no Ir element signal was detected by M-STO in the physically mixed TiO2 and SrTiO3 sample.

[0042] Experimental Example 2 A certain amount of the catalysts prepared in Examples 1-6 were weighed and analyzed by TEM. The results are as follows: Figure 3 As shown, the prepared sample is a nanoporous material with uniform particle distribution. The nanoparticles are of uniform size, well-dispersed, and show no obvious agglomeration. Furthermore, no large iridium-based particles are observed in the STEM image; the noble metal iridium is uniformly dispersed within the SrTiO3-TiO2 dual-phase support lattice, confirming the successful preparation of a precisely doped Ir heterostructure nanoparticle catalyst. The catalyst structure prepared in this application is beneficial for mass transfer, charge transfer, and timely release of generated gases during electrochemical reactions. STEM-EDS analysis shows that with increasing Ir doping concentration, the Sr element distribution decreases, while the Ti element distribution increases.

[0043] Experimental Example 3 Examples 1-6 were directly used as the working electrode for the hydrogen evolution catalytic reaction at the anode of water electrolysis; a three-electrode system with a saturated calomel electrode of Hg / Hg2Cl2 as the reference electrode and a graphite rod as the counter electrode was used for linear scan testing in a 0.5 mol / L sulfuric acid solution at a scan rate of 5 mV / s. -1 See results Figure 4 , Figure 4 Examples 1-6 were prepared at 0.5 mol L. -1 The linear scan test curve in sulfuric acid was obtained from... Figure 4 It can be seen that the STO-2 catalyst prepared in Example 3 reaches a current density of 10 mA cm⁻¹. -2 The required overpotential was 260 mV. This overpotential was lower than that of the other examples. The results show that Example 3 (STO-2), with a Ti to Ir cation doping ratio of 3:2, exhibited the best OER activity.

[0044] Test Example 4 Comparative Examples 1-2 were directly used as the working electrode for the hydrogen evolution catalytic reaction at the anode of water electrolysis. A three-electrode system was used, with a saturated calomel electrode (Hg / Hg₂Cl₂) as the reference electrode and a graphite rod as the counter electrode. Linear scan tests were performed in a 0.5 mol / L sulfuric acid solution at a scan rate of 5 mV / s. -1 See results Figure 5 Comparative Examples 1-2 and Example 3 were prepared at 0.5 mol / L. -1 The linear scan test curve in sulfuric acid was obtained from... Figure 5 It can be seen that the STO-2-300 and STO-2-400 catalysts prepared in Comparative Examples 1-2 achieve a current density of 10 mA cm⁻¹. -2 The required overpotentials were 264 mV and 269 mV, respectively. Both overpotentials were slightly higher than those of Example 3 (260 mV) without calcination treatment. The above test results demonstrate that further calcination of Example 3 (STO-2) in air atmosphere does not improve its OER catalytic activity.

[0045] Experimental Example 5 A proton exchange membrane water electrolyzer (PEMWE) was constructed using (STO-2) prepared in Example 3 as the anode and commercial Pt / C as the cathode catalyst. (See [link to relevant documentation]). Figure 6 At 80°C, the loading was 1 mg cm. -2 The electrode performed better than the one with a loading of 2 mg cm⁻¹ at all tested current densities. -2 IrO2. The loading amount was 2 mg cm⁻¹. -2 The STO-2 electrode at 3 A cm -2 It reached 1.75V, exceeding the 1.8V (3 A cm⁻¹) target set by the U.S. Department of Energy for 2026. -2 ) Goal. For example... Figure 7 As shown, the CP curves of the membrane electrode assembly (MEAs) operating at 80°C clearly demonstrate that the use of STO-2 significantly improves the stability of PEMWE. Importantly, the STO-2||Pt / C MEA exhibits good stability at 1 A cm⁻¹. -2 At the specified current density, the battery voltage did not increase significantly over a duration of 1300 hours. The degradation rate of STO-2||Pt / C was 0.0296 mV / h. -1 The degradation rate is far lower than that of IrO2||Pt / C (5.274 mV h). -1 ).

[0046] Depend on Figure 1 It can be seen that the Ir doping ratio has a significant impact on the material. On the one hand, excessive Ir doping disrupts the inherent proportions or tolerance factor of ABO3 perovskite; on the other hand, the increased mass loading of the noble metal Ir affects catalytic costs and leads to an increase in the potential number of IrO2 units. Figure 2 XPS test results confirmed that no Ir element signal was detected in the physically prepared SrTiO3-TiO2 sample, ruling out the possibility that the physically composite sample contained Ir active sites. Figure 3It can be seen that as the Ir doping ratio increases, SrTiO3 gradually transforms into a SrTiO3-TiO2 heterostructure, and eventually becomes the main phase of TiO2. Figure 4 It is known that an appropriate amount of doping can maintain the SrTiO3-TiO2 heterostructure and possess the maximum activity. Figure 5 It is known that an appropriate synthesis temperature can maintain the SrTiO3-TiO2 heterostructure and possess maximum activity. Figure 6 and 7 It can be seen that the STO-2 electrode at 3 A cm -2 It reached 1.75 V, exceeding the 1.8 V (3 A cm⁻¹) target set by the U.S. Department of Energy for 2026. -2 The target was to demonstrate its excellent activity. After a long-term stability test of 1300 hours, STO-2 showed no significant increase in voltage, indicating extremely excellent catalytic stability. Furthermore, the Ir mass loading (~0.122 mg / cm³) was also low. -2 The cost is extremely low, making it suitable for large-scale promotion and utilization.

[0047] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing an Ir-doped TiO2-SrTiO3 heterostructure catalyst, characterized in that, Includes the following steps: S1. Weigh out titanium source, strontium source and iridium source, add them to dilute alkaline solution, stir and react to obtain the first perovskite precursor; S2. Heat the first perovskite precursor until the solution turns blue to activate the precursor. S3. The activated precursor is subjected to a high-temperature hydrothermal reaction to obtain the second composite precursor. S4. Add HNO3 solution to the second composite precursor, sonicate the reaction, and wash and dry after the reaction to obtain Ir-doped SrTiO3-TiO2 heterostructure catalyst.

2. The method for preparing an Ir-doped TiO2-SrTiO3 heterostructure catalyst according to claim 1, characterized in that: In step S1, the titanium source is TiO2, the strontium source is selected from Sr(NO3)2 and Sr(OH)2, and the iridium source is selected from H2IrCl6; the molar ratio of titanium source, strontium source and iridium source is 3~1:5:1~3.

3. The method for preparing an Ir-doped TiO2-SrTiO3 heterostructure catalyst according to claim 1, characterized in that: The dilute alkaline solution in S1 is 0.5-2M KOH solution, and the reaction is carried out at room temperature for 10-24 hours.

4. The method for preparing an Ir-doped TiO2-SrTiO3 heterostructure catalyst according to claim 1, characterized in that: In S2, the endpoint of the reaction is determined by the solution changing from light blue to dark blue.

5. The method for preparing an Ir-doped TiO2-SrTiO3 heterostructure catalyst according to claim 1, characterized in that: The hydrothermal reaction temperature in S3 is 100–400℃, and the holding time is 12–76 hours.

6. The method for preparing an Ir-doped TiO2-SrTiO3 heterostructure catalyst according to claim 1, characterized in that: In S4, the HNO3 solution is a nitric acid aqueous solution with a mass fraction of 25-35%. The total ratio of titanium source, strontium source and iridium source to HNO3 solution is 1:1 to 1:5 mmol / mL. The reaction is sonicated for 10-60 minutes. After the reaction is completed, the mixture is washed with deionized water and ethanol.

7. An Ir-doped TiO2-SrTiO3 heterostructure catalyst, characterized in that: The nanoporous structure is obtained by the preparation method described in any one of claims 1-6.

8. The application of the Ir-doped TiO2-SrTiO3 heterostructure catalyst according to claim 7 in electrocatalytic water splitting for oxygen production.

Citation Information

Patent Citations

  • Iridium-based solid solution perovskite catalyst SrTi(Ir)O3 and its application in electrocatalytic water splitting for oxygen production

    CN109161926B